2022
DOI: 10.14221/aihjournal.v3n3.1
|View full text |Cite
|
Sign up to set email alerts
|

Review of cannabis use among Aboriginal and Torres Strait Islander people

Abstract: The health effects of cannabis use may not always be seen as a high priority for Aboriginal and Torres Strait Islander communities. However, the impact of cannabis use on physical and mental health can have significant consequences. It is known that the use of high potency cannabis has increased over the last two decades, with a corresponding increased risk to health. In particular, young people are at increased risk of experiencing harms to mental health. Physical harms to health include effects on the respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…22 Furthermore, prolonged consumption of kava has been reported that it can cause health impacts especially liver toxicity, raised cholesterol, and dermatitis . 17 While studies on kava in pregnancy are limited worldwide; some authors have suggested that kava consumption should be avoided entirely during pregnancy and lactation because of the uncertainty about its hepatic safety and the possible harm to the unborn baby. 23,24 In our study, the prevalence of maternal history of kava use was only 1% (n = 23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Furthermore, prolonged consumption of kava has been reported that it can cause health impacts especially liver toxicity, raised cholesterol, and dermatitis . 17 While studies on kava in pregnancy are limited worldwide; some authors have suggested that kava consumption should be avoided entirely during pregnancy and lactation because of the uncertainty about its hepatic safety and the possible harm to the unborn baby. 23,24 In our study, the prevalence of maternal history of kava use was only 1% (n = 23).…”
Section: Discussionmentioning
confidence: 99%
“…15 While studies in LMICs have shown betel nut, marijuana, and the use of alcohol may have a direct impact on birth weights, 5,16 effects of kava use on pregnancy have not been studied. 17 Kava is a traditional Pacific Island beverage made from the piper methysticum plant and is becoming increasingly consumed in the Solomon Islands. 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation